Reversible, functional amyloids: towards an understanding of their regulation in yeast and humans. Issue 13 (3rd July 2018) - Cereghetti, Gea; Saad, Shady; Dechant, Reinhard; Peter, Matthias
ABSTRACT: Protein aggregates, and in particular amyloids, are generally considered to be inherently irreversible aberrant clumps, and are often associated with pathologies, such as Alzheimer's disease, Parkinson's disease, or systemic amyloidosis. However, recent evidence demonstrates that some aggregates are not only fully reversible, but also perform essential physiological functions. Despite these new findings, very little is known about how these functional protein aggregates are regulated in a physiological context. Here, we take the yeast pyruvate kinase Cdc19 as an example of a protein forming functional, reversible, solid, amyloid-like aggregates in response to stress conditions. Cdc19 aggregation is regulated via an aggregation-prone low complexity region (LCR). In favorable growth conditions, this LCR is prevented from aggregating by phosphorylation or oligomerization, while upon glucose starvation it becomes exposed and allows aggregation. We suggest that LCR phosphorylation, oligomerization or partner-binding may be general and widespread mechanisms regulating LCR-mediated reversible protein aggregation. Moreover, we show that, as predicted by computational tools, Cdc19 forms amyloid-like aggregates in vitro . Interestingly, we also observe striking similarities between Cdc19 and its mammalian counterpart, PKM2. Indeed, also PKM2 harbors a LCR and contains several peptides with high amyloidogenic propensity, which coincide with known phosphorylation sites. Thus, we speculate that the formation of reversible, amyloid-like aggregates may be a general physiological mechanism for cells to adapt to stress conditions, and that the underlying regulatory mechanisms may be conserved from yeast to humans.